Teachers’ digital competence in the Practicum of a Primary Education Degree: reflections on the use of technology in the classroom - Batlle, Jaume (2024)
Teachers’ digital competence is already considered in teacher training as an essential competence that future teachers must achieve. However, this is still a novel reality that needs to be contrasted with the current reality of teacher education programs. This study seeks to determine how digital teaching competence is developed in the Practicum of the degree in Primary Education at the University of Barcelona. The qualitative analysis focuses on the uses of technology made explicit in the pre-service teachers' reflective portfolios and the characterization of their reflections derived from those uses. The results of the analysis show that pre-service teachers reflect on three distinct uses of digital tools: those observed in the educational context of their Practicum, those used for the creation of materials, and those used for students to develop their digital competence. From these three uses of digital tools, reflections are derived from the students' practical experience. Their reflections are expressed with positive assessments, but mostly in an initial reflective stage: the one in which pre-service teachers establish a mere description of reality. The study's results invite us to propose the need for greater development of awareness of the digital component in teaching, both in the development of their degree studies and throughout the Practicum.